Micrometer and Millimeter Wave P-to-P Links Under Dust Storm Effects in Arid Climates - Shamsan, Z. A.; Alammar, M.; Alharthy, A.; Aldahmash, A.; Al-Snaie, K. A.; Al-Hetar, A. M. (Engineering, Technology & Applied Science Research, 2019)
A dust storm is the main attenuation factor that can disturb receiving radio signals in arid climate condition as in Saudi Arabia. This paper presents a study on the effect of dust storms on the received radio frequency power in a homogenous environment in the city of Riyadh. A number of micrometer and millimeter wave links have been considered along with several measured dust storm data to investigate the dust storm effects. The results showed that dust storm can critically influence the communication link and this effect grows up as the physical distance between the transmitter and the receiver increases. The negative effect of the dust storm apparently appears at high-frequency bands allocated for the next communication generation (5G) which imposes finding solutions to mitigate the effects of this phenomenon.